2017
DOI: 10.4038/kjm.v5i2.7519
|View full text |Cite
|
Sign up to set email alerts
|

Influence of employees’ perceived organizational support and job performance on customer satisfaction: an empirical support from Nepalese hospitality sector

Abstract: This study investigated the interrelationship of Perceived Job Performance (PJP), PerceivedOrganizational Support (POS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The empirical finding of this study reveals that POS is directly related to PJS and PJP. In this study, it was found that POS has significant positive direct effect on PJP, the finding is consistent with past empirical findings of Na-Nan, Saribut and Sanamthong [9], Xiu, Dauner and McIntosh [10], Du et al [11], Byrne and Hochwarter [12], Biswakarma [13], Burmeister and Deller [14], Yaakobi and Weisberg [15], Wickramasinghe and Wickramasinghe [8], Hakkak, Gashti, and Nawaser [1], Guan, Sun, Hou, Zhao, and Luan [17], Armeli, Eisenberger, Fasolo, and Lynch [16], Eisenberger, Huntington, and Hutchison [6], where it was mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization [13]. Burmeister and Deller [14], Yaakobi and Weisberg [15] concluded that perceived environmental support and knowledge sharing as the main factors which can heightened active job performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The empirical finding of this study reveals that POS is directly related to PJS and PJP. In this study, it was found that POS has significant positive direct effect on PJP, the finding is consistent with past empirical findings of Na-Nan, Saribut and Sanamthong [9], Xiu, Dauner and McIntosh [10], Du et al [11], Byrne and Hochwarter [12], Biswakarma [13], Burmeister and Deller [14], Yaakobi and Weisberg [15], Wickramasinghe and Wickramasinghe [8], Hakkak, Gashti, and Nawaser [1], Guan, Sun, Hou, Zhao, and Luan [17], Armeli, Eisenberger, Fasolo, and Lynch [16], Eisenberger, Huntington, and Hutchison [6], where it was mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization [13]. Burmeister and Deller [14], Yaakobi and Weisberg [15] concluded that perceived environmental support and knowledge sharing as the main factors which can heightened active job performance.…”
Section: Discussionsupporting
confidence: 92%
“…Byrne and Hochwarter [12] found that the relationship between perceived organizational support and Job performance. Biswakarma [13] found a significant relationship between perceived job performance and perceived organizational support, and mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization. Likewise, the studies of Burmeister and Deller [14], Yaakobi and Weisberg [15] proposed perceived environmental support and knowledge sharing as the main factors which enhanced effective employee job performance.…”
Section: Perceived Organizational Support and Perceived Job Performancementioning
confidence: 99%
“…The findings of the study conducted by Krishnan and Wesley (2018) clearly state that employee communication contributes to person-organization fit through POS, learning and development and job characteristics. Similarly in yet another study, POS partially mediated JIBR 13,1 the relationship between perceived job performance and customer satisfaction in the hospitality sector in Nepal (Biswakarma, 2016).…”
Section: Perceived Organizational Supportmentioning
confidence: 57%
“…Training and development, performance reviews, and employee involvement all have a good and significant impact on employee motivation. One of the most crucial and challenging aspects of managing human resources, according to Biswakarma (2016), is separating the performers from the non-performers and creating an environment in which the former is rewarded and driven to do even better while the latter are recognized.…”
Section: Statement Of the Problemmentioning
confidence: 99%